Modern Study of Philanthropy in Russia: Historical and Legal and Humanitarian Aspects - V. Vlasov, B.; A. Dabagyan, A.; A. Zaitseva, E.; G. Ryzhakov, D.; V. Trofimova, Yu. (International Journal of Engineering and Technology, 2018)
An attempt to comprehend the main fields of study of various aspects of philanthropy in the Russian Empire at the end of the 19th â€“ early 20th centuries is presented in this article. The aggregate of sources considered on this topic can be conditionally divided into two large groups: the first group â€“ modern domestic publications of both a monographic and a periodic nature; the second group â€“ the English-language historiography presented by university editions. The article provides an overview of various approaches to the history of philanthropy in the latest specialized scientific journals. The methodology of the article is based on a comparative chronological analysis of numerous publications on the theme of philanthropy in the Russian Empire, as well as the principles of objectivity and historicism.Â